Effect of Foreign Shareholdings and Originating Countries on Banking Sector Efficiency. Issue 9 (1st September 2016) - Chan, Sok-Gee; Koh, Eric H. Y.; Kim, Yong-Cheol
ABSTRACT: We analyze how foreign shareholdings affect the ASEAN-5's banking sector efficiency using stochastic frontier analysis. Unlike most extant studies, which compare the performance of local and foreign banks, we assess how foreign shareholdings affect bank efficiencies. We also apply resource-based theory to analyze whether the foreign shareholdings' countries of origin matter. We find that foreign shareholders from more developed countries enhance the bank's resource base. Those from Asia have the greatest effect, perhaps because of their proximity and familiarity. Moreover, excessive regulation stifles the host countries' profit efficiency potential. Finally, foreign shareholding concentration potentially enhances efficiencies by reducing agency costs.